Torsional Strength of Reinforced Concrete Beams with Brine and Olive Oil Mill Wastewater - Hamadallah Al-Baijat; Husein A. Alzgool (Salehan Institute of Higher Education, 2023)
The authors conducted a comprehensive research study on adding olive oil mill and brine wastewater to the concrete mix to investigate torsion, bending stress, shear, and compressive strength. The total number of specimens were 33 beams 100 mm (depth) × 100 mm (width) × 500 mm (length). Three beams were used as control samples, and thirty beams were divided into two groups: fifteen samples were from an olive oil mill, and the other fifteen were brine wastewater with different percentages of additive material (olive oil mill and brine wastewater), with 2.5, 5.0, 7.5, 10.0, and 15.0 % of each. The beams were reinforced with 4 ϕ 8 mm as longitudinal steel bars and ϕ 4 mm stirrups spaced at 20 mm. All specimens were tested at 28 days. It was found that the torsional strength of the samples containing brine wastewater when added at the best percentage, which is 10%, was 5.46 MPa. As is the case when adding olive oil mill wastewater with the best percentage, which is 7.5%, it was 5.16 MPa. These data are greater than the torsional strength in the reference samples, which were 4.38 MPa, meaning that the torsional strength when adding brine wastewater and olive oil mill wastewater increases by 24% and 17%, respectively. Doi: 10.28991/CEJ-2023-09-03-012 Full Text: PDF